Research Progress and Engineering Applications of Viscous Fluid Mechanics - Jianjun Peng; Run Feng; Meng Xue; Erhao Zhou; Junhua Wang; Zhidan Zhong; Xiangchen Ku (Applied Sciences)
This paper systematically reviews the development of viscous fluid mechanics and expounds the current research status of viscous fluid mechanics from the aspects of permeability experiments and research on viscous fluids, particle distribution and movement, droplet impact, modern computer technology simulation, etc. This paper summarizes the application status of viscous fluid mechanics theory in aerospace, fluid simulation, bioengineering, pipeline transportation, and other engineering fields, analyzes the influence of multiphysical field coupling, complex flow, and new materials on viscous fluid mechanics, and puts forward its development trend in algorithms, simulation, biomedicine, aerospace, and other fields.